2022
DOI: 10.1039/d1nr07434b
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Doped black phosphorus quantum dots as multifunctional Fenton nanocatalyst for boosting synergistically enhanced H2O2-guided and photothermal chemodynamic cancer therapy

Abstract: Chemodynamic therapy (CDT) is a cancer treatment that converts endogenous H2O2 into hydroxyl radicals (˙OH) through Fenton reaction to destroy cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…10,11 CDT is an emerging tumor therapy strategy that utilizes tumor in situ hydrogen peroxide (H 2 O 2 ) as a raw material to generate hydroxyl radicals (•OH) to kill tumor cells under the catalysis of Fenton/Fenton-like catalysts (Mn 2+ , Cu + , Fe 2+ , etc.). 6,12,13 However, the high content of GSH (up to 10 mM) and the low content of H 2 O 2 (100 μM) in TME limit the efficiency of CDT. 4,9,14 Glucose oxidase (GOD) can catalyze glucose to produce abundant H 2 O 2 for Fenton-like reactions to enhance the CDT effect.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 CDT is an emerging tumor therapy strategy that utilizes tumor in situ hydrogen peroxide (H 2 O 2 ) as a raw material to generate hydroxyl radicals (•OH) to kill tumor cells under the catalysis of Fenton/Fenton-like catalysts (Mn 2+ , Cu + , Fe 2+ , etc.). 6,12,13 However, the high content of GSH (up to 10 mM) and the low content of H 2 O 2 (100 μM) in TME limit the efficiency of CDT. 4,9,14 Glucose oxidase (GOD) can catalyze glucose to produce abundant H 2 O 2 for Fenton-like reactions to enhance the CDT effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Interestingly, MnO 2 nanosheets are an appealing GSH-responsive material, and the released Mn 2+ can be not only for MRI but also as a catalyst for chemodynamic therapy (CDT). , CDT is an emerging tumor therapy strategy that utilizes tumor in situ hydrogen peroxide (H 2 O 2 ) as a raw material to generate hydroxyl radicals (·OH) to kill tumor cells under the catalysis of Fenton/Fenton-like catalysts (Mn 2+ , Cu + , Fe 2+ , etc. ). ,, However, the high content of GSH (up to 10 mM) and the low content of H 2 O 2 (100 μM) in TME limit the efficiency of CDT. ,, Glucose oxidase (GOD) can catalyze glucose to produce abundant H 2 O 2 for Fenton-like reactions to enhance the CDT effect. In addition, photothermal therapy (PTT) can accelerate the Fenton-like reaction and enhance CDT while ablating tumor cells by hyperthermia. , Moreover, the targeting ability of materials is crucial in tumor diagnosis and treatment. , It has been reported that cell membrane-coated nanoparticles can greatly improve the biosafety of nanocatalysts, enabling it to escape the immunity system and improve homologous targeting to parental cells through self-recognition and internalization by cancer cell lines. …”
Section: Introductionmentioning
confidence: 99%
“…Among the liquid metals, an important class is eutectic gallium-indium alloys, which can produce ROS under microwave radiation. (4) Fenton catalysts (e.g., iron ions, copper sulfide, Cu I , and Mn 2+ ) can mediate the Fenton reaction to achieve redox reactions and promote the generation of ROS [38][39][40]. Iron ions are the most widely studied metal ions with Fenton activity and have recently been popularly researched.…”
Section: Oxidative Modulatorsmentioning
confidence: 99%
“…21 As a Fenton-like reagent, copper has redox properties similar to those of iron. 22 Cu + can react with H 2 O 2 to form •OH and Cu 2+ , which can occur with considerable efficiency in slightly acidic and neutral media. 23−25 Currently, great efforts have been paid to increasing the H 2 O 2 content to improve the CDT efficacy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, iron-based nanomaterials are widely used as Fenton reagents for CDT. However, the Fe 2+ -mediated Fenton reaction is only effective in strongly acidic media (pH = 2–4) . As a Fenton-like reagent, copper has redox properties similar to those of iron . Cu + can react with H 2 O 2 to form •OH and Cu 2+ , which can occur with considerable efficiency in slightly acidic and neutral media. …”
Section: Introductionmentioning
confidence: 99%